PATTERN AND EXTENT OF ADVERSE DRUG REACTIONS (ADRS) WITH ANTIEPILEPTIC DRUGS AEDS - Rahul wagh, Sudhir Padwal, Shrikant Dharmadhikari, Vinod Deshmukh, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
There are additional challenges associated with anti-epileptic medications,such ADRs and compound interactions. The findings of systematic reviews and metaanalyses examining prospective research